Effect Of 8% Ethyl Acetate Fractionated Coriander Seed (Coriandrum sativum) Extract Gel on The Number of Neutrophils and Fibroblasts in The Healing Process of Gingivitis (in vivo Study on Wistar Rats) - Sanjaya, Devita; Nur, Asikin; Kuswandari, Sri (Interdental Jurnal Kedokteran Gigi (IJKG), 2025)
Introduction: Gingivitis is inflammation of the gingiva and the initial stage of periodontal disease, which, if not treated, will become periodontitis. Coriander seeds (Coriandrum sativum) have anti-bacterial and anti-inflammatory properties. This study aimed to determine the effect of 8% ethyl acetate fractionated coriander seed extract gel on the number of neutrophils and fibroblasts in the healing process of gingivitis (in vivo) in Wistar rats. Material and Method: Thirty-six rats were divided into 3 groups: the 8% ethyl acetate fractionated coriander seed extract gel group, the chlorhexidine gel group, and the placebo gel group. Gingivitis was induced by tying a silk ligation to the subgingival area of ​​the lower incisor for 7 days. 0.05 ml of gel was applied twice a day in the gingivitis area. On days 1, 3, 5, and 7, three rats from each group were decapitated, histological preparations were made with HE staining, and the number of neutrophils and fibroblasts was counted using an Optilab microscope with 400x magnification. Healing assessment was measured based on the decrease in the number of neutrophils or the increase in the number of fibroblasts compared to the number of neutrophils or fibroblasts on the initial observation day. Results and Discussions: A significant difference in neutrophil counts was found in the 8% ethyl acetate fractionated coriander seed extract gel group (45.43%) and the placebo gel group (51.67%) on days 3. A significant difference was also found in the number of fibroblast in the 8% ethyl acetate fractionated coriander seed extract gel group (5410%) and the placebo gel group (4470%) on days 5, and between the 8% ethyl acetate fractionated coriander seed extract gel group (8463.33%) and the placebo gel group (7953.33%) on days 7. Conclusion: This research concludes that 8% ethyl acetate fractionated coriander seed extract gel can reduce the number of neutrophils and increase the number of fibroblasts in the gingivitis healing process.